DISKRIMINASI SOSIAL PEREMPUAN ODHA : ANALISIS PERATURAN DAN PERLINDUNGAN HUKUM: Women with HIV/AIDS and Social Discrimination: Analysis of Regulations and Legal Protection - Rizqi Amalia Tsani; Retnowulandari, Wahyuni (Faculty of Law, Universitas Trisakti, 2025)
HIV/AIDS is a global health issue, including in Indonesia. Despite efforts to combat it, stigma and discrimination against people living with HIV/AIDS (PLWHA), especially women with HIV/AIDS, remain significant barriers to achieving social welfare and justice. This study aims to describe the legal protection of women living with HIV and analyze regulations related to social stigma and discrimination faced by women living with HIV. This research uses normative research methods, with analysis of legislation, by analyzing laws and regulations, such as Law No. 39/1999 on Human Rights, CEDAW 1984, and Minister of Health Regulation No. 21/2013 on HIV and AIDS Prevention. The findings show that while there are regulations intended to eliminate discrimination against PLWHA, the reality on the ground reveals that discrimination against women with HIV/AIDS, such as verbal abuse, avoidance, and social exclusion, still occurs frequently, highlighting a gap between legal regulations in society. This study recommends the importance of improving the strengthening of policies that are more responsive to the needs of women living with HIV, in order to create a more inclusive and equitable environment for all parties.